What constitutes effective EP support for CYP with SEMH needs? Exploring SENCos’ post-coronavirus perspectives using Q-methodology. - Kershaw, Abigail Frances (2025)
Children and young people’s (CYPs’) social, emotional and mental health (SEMH) has been a priority for multiple UK policies and strategies aimed at improving support. The 2020 coronavirus pandemic exacerbated existing mental health challenges among vulnerable populations, including secondary school-aged CYP. Existing supply-and-demand challenges for targeted support were amplified, and the pressure on schools to provide early intervention increased. Special educational needs coordinators (SENCos) are key in coordinating this support, often in collaboration with educational psychologists (EP). Thus, SENCos are well-placed to offer insights into the most effective EP approaches for supporting secondary school-aged CYPs’ SEMH needs in the post-coronavirus context.